OPTIMIZED MEASURES FOR CORRECTION OF DENTAL STATUS IN PROFESSIONAL ATHLETES - Safaraliev, F.R. (World of Medicine and Biology, 2020)
The clinical state of the oral cavity, the functional state of the salivary glands, and the effectiveness of therapeutic and preventive measures using propolis-based medicine (Balsam Pomegranate) were studied in 122 professional wrestlers aged 18 to 34 years. In the course of our observations it has been ascertained fact in digital values and a significant reduction of unfavorable background unstimulated salivary secretion in subjects athletes at the studied length of stay in prolonged intense psycho-emotional and physical condition. Status of oral hygiene and periodontal tissues in the study group of athletes who have practically healthy periodontium, deteriorated after an intensive training process at almost 1.5 times. Preparation "Balsam Pomegranate" has a very important, especially with the preventive point of view, antiinflammatory, organoleptic properties, as based on the natural stimulation help to improve the hygienic condition of the oral cavity, the state of periodontal tissues, as well as a pronounced stimulation of salivation and increasing salivary flow rate.
Keywords: periodontitis; saliva; hygiene; intense exercise; prevention